2022
DOI: 10.1101/2022.11.29.518320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cell wall lipoprotein CD1687 acts as a DNA binding protein during deoxycholate-induced biofilm formation inClostridioides difficile

Abstract: The ability of bacterial pathogens to establish recurrent and persistent infections is frequently associated with their ability to form biofilms. Clostridioides difficile infections have a high rate of recurrence and relapses and it is hypothesised that biofilms are involved in its pathogenicity and persistence. Biofilm formation by C. difficile is still poorly understood. It has been shown that specific molecules such as deoxycholate (DCA) or metronidazole induce biofilm formation, but the mechanisms involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…In addition, several genes encoding putative membrane and cell wall proteins of unknown function as well as lipoproteins are up-regulated in the presence of succinate (Table S2). We noted that the lipoprotein CD1687 recently demonstrated to be essential in the DCA-induced biofilm (10,45) is not regulated by succinate and confirmed that a CD1687 mutant is not affected in biofilm formation in the presence of this inducer (Figure 4a).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, several genes encoding putative membrane and cell wall proteins of unknown function as well as lipoproteins are up-regulated in the presence of succinate (Table S2). We noted that the lipoprotein CD1687 recently demonstrated to be essential in the DCA-induced biofilm (10,45) is not regulated by succinate and confirmed that a CD1687 mutant is not affected in biofilm formation in the presence of this inducer (Figure 4a).…”
Section: Resultssupporting
confidence: 76%
“…On the other hand, lipoproteins which are involved among other things in nutrient uptake and signalling systems (52), may be able to detect extracellular succinate. We recently demonstrated that the lipoprotein CD1687 of the 630Δ erm strain mediates in part the metabolic reorganization occurring in DCA-induced biofilm (10,45). Since CD1687 is not involved in succinate-induced biofilm formation, we cannot exclude that lipoproteins up-regulated in the presence of succinate (Table S2), could sense succinate and/or induce metabolic pathways involved in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%